Serial assessment of early antibody binding to decellularized valved allografts - Oripov, Firdavs; Ramm, Robert; Falk, Christine; Goecke, Tobias; Ebken, Johannes; Jashari, Ramadan; Böthig, Dietmar; Horke, Alexander; Avsar, Murat; Bobylev, Dmitry; Haverich, Axel; Hilfiker, Andres; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives: Decellularized homograft valves (DHV) appear to elicit an immune response despite efficient donor cell removal. Methods: Semi-quantitative Dot-Blot analysis for preformed and new recipient antibodies were performed in 20 patients following DHV implantation on day 0,1,7,28 using secondary anti-human antibodies. Immune reactions were tested against the implanted DHV as well as towards stored samples of 5 non-implanted decellularized aortic (DAH) and 6 pulmonary homografts (DPH). Results: 20 patients were prospectively included to the study, median 18 years, IQR 12-30 years, 3 female and 17 male patients. Six patients received DPH and 14 DAH. The amount of antibody binding, averaged for all patients, decreased on postoperative day 1 and 7 in comparison to preoperative values and on day 28 reached almost preoperative extent (16.8±2.5 on day 0, 3.7±1.9 on day 1, 2.3±2.7 on day 7 and 13.2±3.7 on day 28). Parallel to the results in healthy controls there was higher amount of antibody binding towards DAH than DPH. The mean number of arbitrary units was 18.4±3.1 in aortic and 12.9±4.5 in pulmonary DHV (p=0.140). Male patients exhibited clearly higher antibody binding towards aortic DHV than female patients (19.5±2.1 vs. 1.6±6.7). P-value calculation was limited by only 2 female patients receiving DAH. There was no correlation of the amount of overall antibody binding to DHV with respect to donor age, Kruskal-Wallis test p=0.550. DHV recipients with a sex mismatch to the donor showed significantly less antibody binding (6.5±1.8 vs 13.7±1.8; p=0.003). The main finding was the increase of antibody binding in younger patients receiving decellularized aortic allografts. This increase was enhanced in patients with early degeneration signs, but that increase was not specific for the implanted DHV nor previous DHV implantation. Antibody binding towards explanted DHV was significantly increased implicating antibody mediated DHV degeneration. Conclusion: Serial assessment of tissue-specific antibody binding revealed an increase within four weeks after surgery in some patients, who subsequently developed early signs of allograft degeneration. Studies with larger sample size are needed to confirm the prognostic relevance of antibody increase as well as specific research efforts to identify the molecular agents triggering such antibody response.